Experience, Nature and Art - John Dewey (Revista Apotheke, 2022)
Translation Note: This translation refers to the original 1925 essay published by John Dewey in the Journal of the Barnes Foundation, in which he was a member as Director of Education.
Keywords: Experiencia; Nature; Art; Aesthetics; Pragmatism